APLIKASI PLC OMRON CP1E 30 I/O PADA TRAINING KIT ELECTROPNEUMATIC - , AGUS PRAYITNO; , Andhi Akhmad Ismail., ST.,M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Automation control is needed in the industry today as facilitate oversight, implementation and requires fewer workers. One of the tools that are needed in the automation control PLC (Programmamble Logic Controller). Made in order to facilitate learning as a training tool kit. PLC To make this training kit is more easily learned by students and more similar to the industry then this training kit consists of a (Programmamble Logic Controller) and Electropneumatic. After training kit is made easier, students are expected to understand and know how to work with the automation control system using PLC (Programmamble Logic Controller) which is connected to the Electropneumatic.